Pengaruh Keteladanan Orang Tua Terhadap Pembentukan Akhlak Anak di Madrasah Diniyah Assalam Karangwungu Balongpanggang Gresik - Abdul Natsir; Fathur Rofi'i; Crisafa Naufal Rachmawan (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
ABSTRACT This study aims to determine the effect of parental role modeling on the moral development of children at Madrasah Diniyah Assalam Karangwungu Balongpanggang Gresik. The background of this research lies in the essential role of parents as the first educators in instilling moral values that shape children’s social and religious life. This research employed a quantitative method with an ex post facto approach. The population consisted of all students of Madrasah Diniyah Assalam, with a randomly selected sample of 30 respondents. Data were collected through questionnaires and documentation, then analyzed using validity and reliability tests, normality tests, simple linear regression, and t-test with the assistance of SPSS. The findings revealed that parental role modeling has a significant effect on the moral development of children, indicated by a t-value greater than the t-table and a significance value less than 0.05. Thus, the better the parental role modeling, the better the children’s moral development. This study highlights the urgent role of family in moral education and provides practical implications for parents and educational institutions to work together in instilling moral and religious values. Keywords : Parental Role Modeling; Children’s Morality; Islamic Education